Observational Study of a French and Belgian Multicenter Cohort of 23 Patients Diagnosed in Adulthood With Mevalonate Kinase Deficiency. Issue 11 (March 2016) - Durel, Cécile-Audrey; Aouba, Achille; Bienvenu, Boris; Deshayes, Samuel; Coppéré, Brigitte; Gombert, Bruno; Acquaviva-Bourdain, Cécile; Hachulla, Eric; Lecomte, Frédéric; Touitou, Isabelle; Ninet, Jacques; Philit, Jean-Baptiste; et al.
Abstract : Abstract: The aim of this study was to describe the clinical and biological features of Mevalonate kinase deficiency (MKD) in patients diagnosed in adulthood. This is a French and Belgian observational retrospective study from 2000 to 2014. To constitute the cohort, we cross-check the genetic and biochemical databases. The clinical, enzymatic, and genetic data were gathered from medical records. Twenty-three patients were analyzed. The mean age at diagnosis was 40 years, with a mean age at onset of symptoms of 3 years. All symptomatic patients had fever. Febrile attacks were mostly associated with arthralgia (90.9%); lymphadenopathy, abdominal pain, and skin lesions (86.4%); pharyngitis (63.6%); cough (59.1%); diarrhea, and hepatosplenomegaly (50.0%). Seven patients had psychiatric symptoms (31.8%). One patient developed recurrent seizures. Three patients experienced renal involvement (13.6%). Two patients had angiomyolipoma (9.1%). All but one tested patients had elevated serum immunoglobulin (Ig) D level. Twenty-one patients had genetic diagnosis; most of them were compound heterozygote (76.2%). p.Val377Ile was the most prevalent mutation. Structural articular damages and systemic AA amyloidosis were the 2 most serious complications. More than 65% of patients displayed decrease in severity and frequency of attacks with increasing age, but only 35% achieved remission. MKD diagnosed in adulthood shared clinical and genetic features with classical pediatric disease. An elevated IgD concentration is a good marker for MKD in adults. Despite a decrease of severity and frequency of attacks with age, only one-third of patients achieved spontaneous remission.